Mindfulness and Mantra Training for Disaster Mental Health Workers in the Philippines - Waelde, Lynn (Archīum Ateneo, 2017)
Disaster mental health training programs have begun to include mindfulness instruction, though better understanding of providers’ mindfulness training expectancies and the differences that disaster exposure might make in their personal practice and clinical utilization of mindfulness is needed to support the feasibility and acceptability of this training in challenging disaster settings. This study examined training expectancies and utilization of a manualized mindfulness meditation and mantra program (Inner Resources for Stress) among N = 68 counselors and psychologists living in the Philippines beginning 12 weeks after Typhoon Haiyan. They attended a 4-h workshop conducted in Manila, Philippines, followed by an 8-week home study program. Following the workshop, a majority had high expectancies that the training would help with survivor and self-care. Higher disaster exposure (β = 0.32) and training expectancies (β = 0.25), but not baseline stress symptoms, were associated with higher perceived usefulness of the training for disaster work. Growth curve analyses demonstrated significantly different trajectories of weekly mindfulness practice for disaster-exposed versus nonexposed participants, with a flatter slope for disaster-exposed participants, though both groups had significant increases in practice time across the 8 weeks (d = 1.71). Higher total number of minutes of mindfulness practice was associated with lower depression severity (β = − 0.34), but not anxiety, at 8 weeks post-training. Participants perceived the training as credible and useful for disaster work and self-care and reported active personal and professional use of the techniques, suggesting that mindfulness training shows promise as a disaster intervention component.